Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan - Setiawan, Marwan; Santobi, Ekon (JUMANJI (JURNAL MANAJEMEN JAMBI), 2024)
One of the most important assets owned by a company is human resources because it has an influence on the survival of the company. Employees in a company should be provided with a comfortable working environment to produce optimal performance. The work environment is an important thing to be considered by every company and is one of the factors that determine employee performance. The purposes of this research are to know how is the work environment, employee performance and how much is the impact of work environment to employee performance. This research was conducted by distributing questionnaires to 25 employees at the Division of Mill Service Departemen PT Lontar Papyrus Pulp And Paper Industry(PT. LPPPI). Based on research that has been done, the regression equation Y =16,322+0,535X . The study states the working environment and employee performance in the Department of Mill Service Departemen PT Lontar Papyrus Pulp And Paper Industry(PT. LPPPI) has a positive relationship (moderate) with a value of 0,535 and the working environment influence on employee performance.